2001
DOI: 10.1002/polb.10041
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the elution behavior in temperature rising elution fractionation and melting in the solid‐state and in the presence of a diluent of polyethylene copolymers

Abstract: Compositionally homogeneous poly(ethylene-␣-olefin) random copolymers with 1-butene and 1-hexene comonomers have been studied. The melting of solutioncrystallized specimens of these copolymers in the presence of trichlorobenzene as a diluent with differential scanning calorimetry (DSC) is well correlated with analytical temperature rising elution fractionation (A-TREF) elution temperature profiles. This indicates that the A-TREF experiment is essentially a diluent melting experiment. Furthermore, the correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In particular, the linear relationship can be verified from the plots of crystallinity and melting temperature against elution temperature. These results are in accordance with those of Hosoda and Mirebella 20, 21. In this article, LLDPE is a copolymer of ethylene and 1‐butene, and the content and distribution of SCB are the key factors to its melting temperature and crystallizability.…”
Section: Resultssupporting
confidence: 90%
“…In particular, the linear relationship can be verified from the plots of crystallinity and melting temperature against elution temperature. These results are in accordance with those of Hosoda and Mirebella 20, 21. In this article, LLDPE is a copolymer of ethylene and 1‐butene, and the content and distribution of SCB are the key factors to its melting temperature and crystallizability.…”
Section: Resultssupporting
confidence: 90%
“…After the polymer solution has been loaded onto TREF column H, three‐way valve E switches position from 1‐2 to 1‐3 to bypass the elution solvent from flowing through TREF column H. When the three‐way valve is at position 1‐3 ( Figure ), the eluting solvent goes through route 1‐3‐12 before passing through transfer line T. Being at stationary state, the TREF column undergoes a programmed‐cooling procedure at a given rate, during which polymers in the solution slowly precipitate from the solvent according to their crystallizability, [ 1,43–45 ] coating onto the inert packing material in the TREF column. As is well known, the separation efficiency is strongly determined by the cooling program.…”
Section: Methodsmentioning
confidence: 99%
“…That limitation is introduced by defining a minimum in the number of monomers in a crystallizing block, n lim . Such limit is related with the maximum value, n max , according to Equation (8). The value of k is also dependent on cooling conditions and consequently is assumed to be an adjustable parameter.…”
Section: Thermodynamic Modelmentioning
confidence: 99%
“…However, previous work of Mirabella demonstrated the correlation between results for ethylene/α‐olefin copolymers obtained from DSC and from modern analytical techniques such as CrystaF and TREF . Murphy et al compared the use of FT‐IR and DSC for the study of melting and crystallization of poly(caprolactone) and concluded that DSC technique was the more useful technique for such a determination.…”
Section: Introductionmentioning
confidence: 99%